Tanggap Pertumbuhan dan Hasil Cabai (Capsicum annuum L.) terhadap Inokulasi Fungi Mikoriza Arbuskula pada Tanah Ultisol - Purnomo, D. Wasgito; Purwoko, Bambang S.; Yahya, Sudirman; Sujiprihati, Sriani; Mansur, Irdika; Amisnaipa, , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The aim of this research was to test the utilization of arbuscular mycorrhizal fungus (AMF) to improve adaptation ability of chili to aluminum (Al) stress based on growth and yield response in four genotypes of chili (Capsicum annuum L.). The research was carried out at University Farm of IPB in Cikabayan from September 2006 to Maret 2007. The media was Ultisol from Gajrug (Lebak, Banten) in polybag. Four genotypes of chili, PBC 619 and Jatilaba (Al tolerant genotypes), and Cilibangi 3 and Helm (Al sensitive genotypes) were treated with and without inoculation of Gigaspora margarita, and planted further in media without Al stress (Al saturation 0.77%) and Al stress (Al saturation 60.85%). Variables observed were degree of AMF infection, root length, plant height, shoot dry weight, number of harvested fruits, fruit length, fruit weight and weight of harvested fruits. The results showed that inoculation of G. margarita effectively decreased negative influence of Al stress by increasing plant height, shoot dry weight, number of harvested fruit, fruit length, weight per fruit and weight of harvested fruits. Inoculation of G. margarita to Al sensitive genotypes was more advantageous than to tolerant genotypes. The Al sensitive genotypes were adapted to Al stress if they were inoculated with G. margarita. In Al stress condition, inoculation of G. margarita to Al sensitive genotypes increased weight of harvested fruits up to 94.49% in Cilibangi 3 and 80.37% in Helm. Key words: Adaptation, aluminum stress, arbuscular mycorrhizal fungus, Capsicum annuum L., Ultisol